Diaspora, identity, and religion : new directions in theory and research - Kokot, Waltraud; Tölölyan, Khachig; Alfonso, Carolin, 1969- (London ; New York : Routledge, 2004)
Examines the development of the concept of diaspora and new perspectives on global networks and local identities. Features case histories on the Caribbean, Irish, Irish-American, Armenian, African and Greek diasporas.
Deconstructing and comparing diasporas / William Safran -- Politics, history and locaiity-- "Too close for comfort" : remembering the forgotten diaspora of Irish women in England / Breda Gray -- Place, movement, and identity : processes of inclusion and exclusion in a Caribbean family / Karen Fog Olwig -- Why locality matters : diaspora consciousness and sedentariness in the Armenian diaspora in Greece / Susanne Schwalgin -- Past and present in the history of modern Greek diaspora / Ioannis K. Hassiotis -- Griots, roots, and identity in the African diaspora / Hauke Dorsch -- The invention of history in the Irish American diaspora : myths of the great famine / Astrid Wonneberger -- Diasporic aspects of religion -- Religion or culture? : concepts of identity in the Alevi diaspora / Martin Sökefeld -- A double minority : notes on the emerging Yezidi diaspora / Andreas Ackermann -- A diachronic view at diaspora, the significance of religion, and Hindu Trinidadians / Martin Baumann -- Let it flow : economy, spirituality, and gender in the Sindhi network / Dieter Haller.
Title from PDF title page (viewed 25 Nov., 2009).
Includes bibliographical references and index.
English.
eBooks on EBSCOhost
Keywords: Emigration and immigration; Ethnic relations -- Political aspects; Group identity; Religious minorities; Space and time -- Social aspects; Emigration and Immigration; Social Identification; Émigration et immigration; Relations interethniques -- Aspect politique; Identité collective; Minorités religieuses; Espace et temps -- Aspect social; group identity; SOCIAL SCIENCE -- Emigration & Immigration; Emigration and immigration; Ethnic relations -- Political aspects; Group identity; Religious minorities; Space and time -- Social aspects; Diaspora; Identiteit; Godsdienst